1994
DOI: 10.1007/bf00043608
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from stem and petiole protoplasts of sweet potato (Ipomoea batatas) and its wild relative, I. lacunosa

Abstract: A protoplast-to-plant regeneration system has been established for sweet potato (Ipomoea batatas (L.) Lam.) and its wild relative, L lacunosa L. Viable protoplasts, isolated from preplasmolyzed stems and petioles of in vitro-grown plants, were cultured on liquid MS (Murashige & Skoog 1962) medium that supported cell division and colony formation. Embryogenic calli of sweet potato were induced on agar-solidified MS medium supplemented with 3% (w/v) sucrose, 50 mg 1-1 casamino acids, 0.2-0.5 mg 1 -l 2,4-D, 1.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Within 3 to 4 weeks, somatic embryos and plantlets with roots and shoots could be successfully regenerated from embryogenic callus derived from the shoot apical meristem (Elliot 1969;Over de Linden and Elliot 1972;Alconero et al 1975;Scaramuzzi and DeGaetano 1983;Jarret et al 1984;Liu and Cantliffe 1984;Chee and Cantliffe 1988;Komaki et al 1989;Chee et al 1990;MandaI and Chandal 1991;AVRDC 1991;Acedo 1991;Schultheis and Cantliffe 1992;Mukherjee et al 1993), stern and root explants (Liu and Cantliffe 1984;Mukherjee et al 1993), leaf explants (Sehgal 1975;Belarmino et al 1992), anther (Kobayashi and Shikata 1975;Sehgal 1978;Tsay and Tseng 1979;Tsay et al 1982;Mukherjee et al 1991), nodal explants MandaI and Chandal1990;Paul et al 1991), petiole explants (Prakash et al 1996), petiole protoplasts (Murata et al 1987), stem and petiole protoplasts (Murata et al 1987;Sihachakr and Ducreux 1987;Belarmino et al 1994), and mesophyll cell suspension (Murata et al 1994). Within 3 to 4 weeks, somatic embryos and plantlets with roots and shoots could be successfully regenerated from embryogenic callus derived from the shoot apical meristem (Elliot 1969;Over de Linden and Elliot 1972;Alconero et al 1975;Scaramuzzi and DeGaetano 1983;Jarret et al 1984;…”
Section: Micropropagationmentioning
confidence: 99%
“…Within 3 to 4 weeks, somatic embryos and plantlets with roots and shoots could be successfully regenerated from embryogenic callus derived from the shoot apical meristem (Elliot 1969;Over de Linden and Elliot 1972;Alconero et al 1975;Scaramuzzi and DeGaetano 1983;Jarret et al 1984;Liu and Cantliffe 1984;Chee and Cantliffe 1988;Komaki et al 1989;Chee et al 1990;MandaI and Chandal 1991;AVRDC 1991;Acedo 1991;Schultheis and Cantliffe 1992;Mukherjee et al 1993), stern and root explants (Liu and Cantliffe 1984;Mukherjee et al 1993), leaf explants (Sehgal 1975;Belarmino et al 1992), anther (Kobayashi and Shikata 1975;Sehgal 1978;Tsay and Tseng 1979;Tsay et al 1982;Mukherjee et al 1991), nodal explants MandaI and Chandal1990;Paul et al 1991), petiole explants (Prakash et al 1996), petiole protoplasts (Murata et al 1987), stem and petiole protoplasts (Murata et al 1987;Sihachakr and Ducreux 1987;Belarmino et al 1994), and mesophyll cell suspension (Murata et al 1994). Within 3 to 4 weeks, somatic embryos and plantlets with roots and shoots could be successfully regenerated from embryogenic callus derived from the shoot apical meristem (Elliot 1969;Over de Linden and Elliot 1972;Alconero et al 1975;Scaramuzzi and DeGaetano 1983;Jarret et al 1984;…”
Section: Micropropagationmentioning
confidence: 99%
“…The callus color changes from light green to light yellow. The bright yellow callus was considered to have higher vigor and was easy to differentiate into embryonic callus (Belarmino et al 1994;Liu Q C et al 2001). The best method for callus induction was solid MS medium fortifed with 0.8 mg L −1 2,4-D. Adventitious roots induction was obtained from callus on solid MS medium with 0.1 mg L −1 to 1.5 mg L −1 6-BA and 0.2 mg L −1 to 1.5 mg L −1 NAA.…”
Section: Resultsmentioning
confidence: 99%
“…Of these various concentrations tested, solid MS medium with ZT 2.0 mg L −1 , KT 1.0mg L -1 and 1.0 mg L −1 GA 3 produce a maximum of number of adventitious shoots after 12 week (Supplementary Table 3). Belarmino et al (1994) reported that plants were regenerated from a single sweet potato callus subcultured on semi-solid MS medium containing 3% (w/v) sucrose, 800 mg L −1 glutamine, 2.0 mg L −1 BA or 1.0 mg L −1 kinetin and 1.0 mg L −1 GA 3 . Up to now, the material that could induce adventitious bud of sweet potato had petiole (Gosukonda RM et al 1995)、leaf(Hg A K.2013)、 Stem fragments (Sihachakr et al1997;Sefasi A et al2013)and callus (Belarmino M,1994) .…”
Section: Resultsmentioning
confidence: 99%